Cooperatively Catalyzed Henry Reaction through Directed Metal‐Chitosan Interactions. Issue 12 (8th October 2019) - Khoury, Christine; Pappuru, Sreenath; Gavriely, Noa; Kleinerman, Olga; Shpasser, Dina; Segal‐Peretz, Tamar; Gazit, Oz M.
Abstract: The main focus of the present work is on identifying the critical parameters involved in inducing acid‐base cooperative catalytic interaction in hybrid metal‐polymer materials. To makes these hybrid materials Ti or Sn acid sites are grafted to the hydroxy groups of chitosan (CS). The cooperative catalytic interactions between the Ti/Sn and the primary amine sites on CS are tested for the nitro‐aldol condensation of nitromethane with 4‐nitro‐benzaldehyde. The observed results show that the synthesis conditions have a pronounce effect on the 3D arrangement of the hybrid materials, which in turn affect the reaction activity and selectivity. The catalysts are characterized using N2 ‐pysisorption, XRD, FTIR, XPS and HRTEM in conjunctions with reaction kinetic analysis. Using the combined results, a reaction mechanism is proposed, which emphasizes the effect of proximity and orientation of the Lewis acid (Ti or Sn) and base (NH2 ) active sites on cooperative catalysis in the Henry reaction. Abstract : Hybrid metal‐polymer materials : The effect of material properties on cooperative interactions between Lewis acid (Ti or Sn) and pendent primary amine sites is evaluated for the nitro‐aldol condensation. Distinctly, the results show that configurational degrees of freedom in the 3D‐structure of hybrid material are critical for inducing efficient cooperative catalytic interactions. However, constraining this structural flexibility (i. e. polymer crosslinking) is key for controlling and enhancing these interactions.